1993
DOI: 10.1063/1.109998
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed laser deposition of epitaxial silicon/h-Pr2O3/silicon heterostructures

Abstract: Epitaxial Si/praseodymium oxide/Si heterostructures were grown in situ on (111) oriented Si substrates using pulsed laser deposition. Growth of the oxide layer under oxygen deficient conditions resulted in hexagonal Pr2O3 (h-Pr2O3) films which displayed a (001)Pr2O3∥(111)Si, [110]Pr2O3∥[11̄0]Si orientation and x-ray rocking curve full width at half-maximum values of ∼0.8°. The top Si layer grew epitaxially on the oxide film with a twinned (111)Si∥(001)Pr2O3 orientation. The surface structure of both oxide and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…3, Pr 2 O 3 forms two polymorphic structures, namely the hex-and the cub-Pr 2 O 3 structure. As-deposited Pr 2 O 3 layers were found to grow in the high temperature (0001) oriented hex-Pr 2 O 3 phase on Si(111) [21,42]. This preference of the high temperature hex-Pr 2 O 3 with respect to the room temperature cub-Pr 2 O 3 phase can be attributed to an epitaxial stabilization given by the far better lattice matching.…”
Section: Contributedmentioning
confidence: 95%
See 1 more Smart Citation
“…3, Pr 2 O 3 forms two polymorphic structures, namely the hex-and the cub-Pr 2 O 3 structure. As-deposited Pr 2 O 3 layers were found to grow in the high temperature (0001) oriented hex-Pr 2 O 3 phase on Si(111) [21,42]. This preference of the high temperature hex-Pr 2 O 3 with respect to the room temperature cub-Pr 2 O 3 phase can be attributed to an epitaxial stabilization given by the far better lattice matching.…”
Section: Contributedmentioning
confidence: 95%
“…Furthermore, Synchrotron radiation X-ray diffraction was applied to study with high resolution and sensitivity the relaxation process from pseudomorphism to bulk behaviour [45]. Interestingly, the epitaxial overgrowth of the hex-Pr 2 O 3 (0001) system by Si was achieved by pulse laser deposition (PLD) [21] as well as by MBE [42]. However, a detailed structure and defect characterization of the epitaxial Si(111) layers revealed a central problem, namely the formation of stacking twins as the major defect mechanism [46].…”
Section: Contributedmentioning
confidence: 99%
“…Fabrication of Pr 2 O 3 films on Si has been performed using molecular beam epitaxy (MBE) [14±16] and pulsed laser deposition. [17,18] Deposited Pr 2 O 3 films are potentially better than other high-k films due to the leakagecurrent densities [19] (< 10 ±8 A cm ±2 at gate voltage (V g ) = +1 V), 10 4 times lower than the observed values for HfO 2 and ZrO 2 films having the same equivalent oxide thickness of 1.4 nm. [20,21] Moreover, Osten et al [22] have reported on Pr 2 O 3 compatibility with conventional complementary metal oxide semiconductor (CMOS) processes, thus demonstrating that it is not necessary to re-engineer manufacturing procedures.…”
mentioning
confidence: 99%
“…The earlier physical vacuum evaporation methods adopted oxidation of the Pr metal layer. [30][31][32] Advanced methods for the fabrication of stoichiometric Pr 2 O 3 and/or PrO 2 films consist of pulsed laser deposition (PLD) [33][34][35] and molecular-beam epitaxy (MBE) [26,[36][37][38] techniques. In particular, the MBE growth of epitaxial Pr 2 O 3 films has been carried out on both Si(001) and Si (111) substrates.…”
Section: Introductionmentioning
confidence: 99%